Clinical and epidemiological characteristics and individual experiences of illness in men with COVID-19: mixed method study - Boas, Andressa Reis de Sousa Vilas; Santos, Daniel Gomes; Teixeira, Jules Ramon Brito; Lourenção, Luciano Garcia; Santos, José Luís Guedes dos; Silva, Richardson Augusto Rosendo da; Carvalho, Ana Raquel Batista de; Sousa, Álvaro Francisco Lopes de; Sousa, Anderson Reis de (São Paulo Medical Journal, 2022)
BACKGROUND: Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, studies have shown that this disease has affected the male population on a significant scale in various parts of the world, making men one of the main risk groups. OBJECTIVE: To analyze the clinical and epidemiological characteristics and experiences of illness in men with COVID-19. DESIGN AND SETTING: A mixed sequential-explanatory study with cross-sectional and exploratory-descriptive approaches. METHOD: Data was collected from a small municipality located in the central-north region of the state of Bahia, Brazil. Primary quantitative data was extracted from compulsory notification forms from 598 men. Qualitative data from individual interviews of 30 men was analyzed by the Discourse of the Collective Subject method. RESULTS: The findings identified the characterization of reports of suspected and confirmed cases of COVID-19 in men, the organization of the healthcare system, and strategies for the control and combat of COVID-19 directed towards the men of the investigated municipality. They revealed the clinical characteristics based on the collective discourse of men with COVID-19. CONCLUSION: In men, the individual experience of disease explicitly explains the clinical markers of COVID-19 expressed by the self-reported syndromic approach. Additionally, this understanding also explains the behaviors observed in their search for health care, as well as the adoption of prevention and control measures and therapies recommended by health professionals.